AP-1/σ1A and AP-1/σ1B adaptor-proteins differentially regulate neuronal early endosome maturation via the Rab5/Vps34-pathway - Candiello, Ermes (Sci Rep, 2016)
The σ1 subunit of the AP-1 clathrin-coated-vesicle adaptor-protein complex is expressed as three isoforms. Tissues express σ1A and one of the σ1B and σ1C isoforms. Brain is the tissue with the highest σ1A and σ1B expression. σ1B-deficiency leads to severe mental retardation, accumulation of early endosomes in synapses and fewer synaptic vesicles, whose recycling is slowed down. AP-1/σ1A and AP-1/σ1B regulate maturation of these early endosomes into multivesicular body late endosomes, thereby controlling synaptic vesicle protein transport into a degradative pathway. σ1A binds ArfGAP1, and with higher affinity brain-specific ArfGAP1, which bind Rabex-5. AP-1/σ1A-ArfGAP1-Rabex-5 complex formation leads to more endosomal Rabex-5 and enhanced, Rab5(GTP)-stimulated Vps34 PI3-kinase activity, which is essential for multivesicular body endosome formation. Formation of AP-1/σ1A-ArfGAP1-Rabex-5 complexes is prevented by σ1B binding of Rabex-5 and the amount of endosomal Rabex-5 is reduced. AP-1 complexes differentially regulate endosome maturation and coordinate protein recycling and degradation, revealing a novel molecular mechanism by which they regulate protein transport besides their established function in clathrin-coated-vesicle formation.